A retrospective look at discovery learning using the Pósa Method in three Hungarian secondary mathematics classrooms - Daunt, Zoe; Saluja, Tarang; Urbanski, Michael; Barbarics, Marta (Teaching Mathematics and Computer Science, 2022)
While the Pósa Method was originally created for mathematical talent management through extracurricular activities, three "average" public secondary school classrooms in Hungary have taken part in a four-year experiment to implement the Pósa Method, which is based on guided discovery learning of mathematics. In this paper, we examine the students’ and teachers’ reflections on the Pósa Method, and how student perspectives have changed between their first and last year of high school. Overall, teachers and students had a positive experience with the Pósa Method. Furthermore, our research indicated that this implementation has met several objectives of the Pósa Method, including enjoyment of mathematics and autonomous thinking. Subject Classification: 97D40